Measuring the association between marginalization and multimorbidity in Ontario, Canada: A cross-sectional study. Issue 1 (10th December 2018) - Moin, John Sina; Moineddin, Rahim; Upshur, Ross Edward Grant
There is growing evidence to suggest that multimorbidity is not only a consequence of aging but also other environmental risk factors such as socio-economic status and social marginalization. In this study, the prevalence of multimorbidity was examined (defined as the simultaneous occurrence of two or more chronic morbidities) by age, gender and the Ontario Marginalization index (material deprivation, residential instability, dependency and ethnic concentration). With a cross-sectional design, 2015 data on 18 morbidities from 12, 516, 587 residents of the province of Ontario, Canada, were analysed. About 82.1% of the population had one or no chronic conditions, 10.3% were multimorbid with two chronic conditions and 7.6% had three or more chronic conditions. The results showed that the prevalence of multimorbidity is noticeably higher in the most deprived areas compared to least deprived for all age groups. Our findings challenge the notion that multimorbidity is primarily driven by aging. Of the 18% of the total population which were multimorbid, 43% of them were under the age of 65. We noted a substantial excess of multimorbidity in younger and middle-aged adults who were most deprived. In some cases, those in the most deprived areas were showing increased cases of multimorbidity nearly 10 years sooner than those who were least deprived. This study shows that environmental factors such as material deprivation and residential instability are correlated with higher prevalence of multimorbidity.